(untitled) (Health Renaissance, 2012)
Background: There are only few studies on the clinico-demographic profile of acute and transient disorders, which is a common disorder in developing countries. Objective: To study the clinical presentation and socio-demographic profile of patients with Acute and transient psychotic disorders. Methods: Thirty patients diagnosed as Acute and transient psychotic disorders were assessed to record their socio-demographic profile, presence of stress, onset, presenting complains and the phenomenology using standard questionnaire. Results: ATPDs was more common in persons below thirty years of age (63.3%), residing in rural areas (90%), unemployed (76.7%), low middle socioeconomic status (53.3%), married (63.3%), and member of nuclear family (63.3%). Abrupt onset was seen in 73% of cases. Delusion of persecution was the most common psychopathology (86.7%). All patients had impaired biorhythm and poor insight. Conclusions: Married unemployed persons below the age of thirty of low middle socioeconomic status residing in nuclear families in rural areas suffer from ATPDs more than others. DOI: http://dx.doi.org/10.3126/hren.v10i3.7138 Health Renaissance; September-December 2012; Vol 10 (No.3);215-219